Assessment of Maximum Mouth Opening of Public Primary and Secondary School Children in Ibadan, Nigeria - O. Popoola; O.O. Gbolahan (Nigerian Dental Association, 2020)
Background: Excessive opening of the mouth has been reported to cause clinical problems such as luxations and traumatic injury to the temporomandibular joint (TMJ). The knowledge of the normal range of mouth opening will help to avoid excessive opening of the mouth which can cause injury to the TMJ of patients during procedures that involve mandibular manipulations. Maximum mouth opening (MMO) has age, race, gender and ethnic variations. Previous studies have looked at normal range of mouth opening among adults, but to the best of our knowledge, no  study has looked at this among the paediatric/children population in Nigeria. Thus, this study aimed to determine the normal maximum mouth opening (MMO) among the paediatric population in Ibadan (South Western part of Nigeria) and the effect of gender, age, height and weight of these children on their MMO. Materials and methods: Six hundred and nine primary and secondary school pupils aged 6 - 15 years were included in this study. Patients with any condition affecting the temporomandibular joint (TMJ) function were not included. Measurements of height, weight and two readings of maximum interincisal distance were performed for each participant. Student's t-test, one-way analysis of variance (ANOVA) and Pearson bivariate correlation were used to assess the sample. Results: The mean MMO was 44.0 ± 5.3 mm and 42.6 ± 5.6 mm for males and females respectively. There was no significant difference in the MMO  of males and females (t= 0.335, p = 0.563). MMO increases gradually with age irrespective of the gender and this was statistically significant (F= 17.1, p =0.001). Conclusion: The maximum mouth opening established for the paediatric population in this study will help practitioners whose care involves the stomathognathic system to have information about the normal range of mouth opening in this group of patients. The result will also be useful asbaseline for future research.